Venous Hypertension Associated with a Posterior Fossa Dural Arteriovenous Fistula: Another Cause of Bithalamic Lesions on MR Images - Greenough, Glen P.; Mamourian, Alex; Harbaugh, Robert E. (American Journal of Neuroradiology, 1999)
Summary: We report a case of a posterior fossa arteriovenous fistula (AVF) with bithalamic hyperintensity on MR images. The thalamic abnormality improved after surgery, suggesting reversible venous hypertension as the pathogenesis of the finding, as opposed to infarction. This manifestation of a posterior fossa AVF should be considered in the differential diagnosis of bilateral thalamic disease.